2019
DOI: 10.1088/1742-6596/1244/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

ICT Strategy and Micro-Entrepreneurs Growth: The Indonesian Case

Abstract: The importance of Information and Communication Technology has been recognized but often undervalued by small businesses. Furthermore, best practices of ICT use in large companies do not always translate to a small business environment. Few studies have been done at the intersection of ICT and Micro and Small Enterprises (MSEs) in a ‘holistic’ manner taking into consideration various aspects of ICT adoption and use. The LIAISE framework provides guidelines for investigating various aspects of ICT adoption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…Including those who specialize in microenterprise. The approach is taken from internet technology and e-business solutions, digital innovation, lean thinking, and various ICT strategies [31]- [34]. The ability of MSMEs, especially in developing nations like Indonesia, to adapt to technology significantly impacts their viability within an increasingly competitive business landscape [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Including those who specialize in microenterprise. The approach is taken from internet technology and e-business solutions, digital innovation, lean thinking, and various ICT strategies [31]- [34]. The ability of MSMEs, especially in developing nations like Indonesia, to adapt to technology significantly impacts their viability within an increasingly competitive business landscape [35].…”
Section: Resultsmentioning
confidence: 99%
“…Banjar has become the centre of industry 4.0 or the digital economy [42]. Therefore, the Smart Banjar concept has been developed in this research, adapted from the Smart Village concept based on [27]- [31] research. Based on the analysis results carried out, it was found that there are differences in the framework dimensions in several pieces of research.…”
Section: Discussionmentioning
confidence: 99%
“…Az interjú vezérfonalának alapját a LIAISE keretrendszer adta -a felépítését 1. ábra mutatja be -, mely a nem kormányzati szervek körében az IKT elfogadásának és használatának feltárására használták a közösségi szervezetek a körében [18]. A LIAISE keretrendszer iránymutatást nyújt a különböző IKT elfogadása és használata szempontjainak vizsgálatára, beleértve az…”
Section: Anyag éS Módszerunclassified
“…• az IKT használatának értékelését (E). [19] Az eredetileg non-profit szektor vizsgálatára kifejlesztett keretrendszer releváns és alkalmazható a kisvállalati szektorban történő IKT-elfogadásának a vizsgálatára [18] [20] [19], mivel a non-profit szektor -sok tekintetben -jelentős hasonlóságokat mutat a kisvállalkozói szektor működésével [1] .…”
Section: Anyag éS Módszerunclassified
“…In terms of technological resources, women micro-entrepreneurs may gain an advantage over their competitors, increasing their likelihood of succeeding and being profitable (Anwar, Djawad, & Ridwansyah, 2019). In today's digital era, people are becoming more literate in information technology.…”
Section: Figure 1 Conceptual Rbv Frameworkmentioning
confidence: 99%